Detection of HBSAG in fixed liver tissue - use of a modified immunofluorescent technique and comparison with histochemical methods. Issue 1 (January 1976) - Portmann, B; Galbraith, R M; Eddleston, A L; Zuckerman, A J; Williams, R
Abstract : A modified immunofluorescent technique was used for the detection of HBSAg in formalin-fixed liver tissue, thereby allowing retrospective examination of paraffin sections and avoiding the need to split the sample at the time of biopsy. Comparison with two other methods, involving either orcein staining or standard haematoxylin and eosin (H and E) preparation for ground glass hepatocytes, showed slightly fewer positive hepatocytes in individual biopsies with the latter stain, but the specificity of both methods was high. In a series of 146 seropositive and 74 seronegative patients with a variety of liver disorders, hepatocytes positive for HBSAg were found in only one of 55 patients with acute hepatitis type B, whereas large numbers of positive cells were seen in all 22 healthy carriers of the surface antigen. In the 69 patients with chronic persistent or chronic aggressive hepatitis, the frequency of positive biopsies was 86% and 85% respectively. The positive cells in these cases were, in comparison with healthy carriers of HBSAg, much fewer in number and were scattered in random fashion throughout the lobule rather than occurring in discrete clumps or sheets. This variation in the intrahepatic expression of HBSAg may reflect differences in the immune response to hepatitis B viral antigens.